d(GGGT)(4) and r(GGGU)(4) are both HIV-1 inhibitors and interleukin-6 receptor aptamers - Magbanua, Eileen (Landes Bioscience, 2013)
Aptamers are oligonucleotides that bind targets with high specificity and affinity. They have become important tools for biosensing, target detection, drug delivery and therapy. We selected the quadruplex-forming 16-mer DNA aptamer AID-1 [d(GGGT)(4)] with affinity for the interleukin-6 receptor (IL-6R) and identified single nucleotide variants that showed no significant loss of binding ability. The RNA counterpart of AID-1 [r(GGGU)(4)] also bound IL-6R as quadruplex structure. AID-1 is identical to the well-known HIV inhibitor T30923, which inhibits both HIV infection and HIV-1 integrase. We also demonstrated that IL-6R specific RNA aptamers not only bind HIV-1 integrase and inhibit its 3′ processing activity in vitro, but also are capable of preventing HIV de novo infection with the same efficacy as the established inhibitor T30175. All these aptamer target interactions are highly dependent on formation of quadruplex structure.